Beyond the Physical World and Sensory Perception: A Philosophical Exploration into the Metaphysical World - Kartanegara, Mulyadhi (Islamic Studies Review, 2022)
This article will address two important subjects in Islamic philosophy that most contemporary modern thinkers (be they philosophers or scientists) have long rejected them as legitimate subjects of any scientific inquiries: firstly, mystical experience, and secondly the metaphysical world. We can see that both subjects lie beyond the physical world and sensory perception. In the first part of this article, I would like to deeply discuss the nature and the reality of mystical experience, while in the second part, I would like to broadly explore the metaphysical world, by first addressing and then moving to analyse two very interesting and seminal works written by arguably two of the most prominent Muslim philosophers, first, Risālat al-Ṭayr authored by Ibn Sīnā, and second, al-Ghurfah al-Gharbiyyah, written by Suhrawardī. It is clear that both works discuss transcosmic voyages into realms beyond our physical world. The purpose of this article is to vividly demonstrate how and why Muslim philosophers, scientists, and mystics substantiate their belief in both realms by establishing a rational argument for their reality or their ontological status.